Koksidiosis pada sapi perah di Kabupaten Jember, Jawa Timur – Indonesia - Nur Muhamad; Aan Awaludin; Yudhi Ratna Nugraheni (Politeknik Negeri Jember, 2021)
This study aims to determine the incidence of coccidiosis in dairy cattle in the Jember District. A total of 75 samples were obtained from Friesian Holstein female dairy cows of varying ages. The materials used were fecal samples, saturated salt (saturated sodium chloride), and distilled water. The method used is a quantitative method with the Mc technique. Master and Whitlock to count oocysts per gram of stool (OPG) found in samples to determine the severity of coccidiosis. Stool samples are taken directly from the rectum of the dairy cattle or taken from the floor of the pen if the dairy cows have just released feces (fresh feces). The stool sample taken for each dairy cow is 10 grams of feces. Identification of the oocysts of Eimeria spp. done qualitatively by using the floating method or the flotation method. The data obtained were analyzed using descriptive analysis, then the prevalance was calculated. The results showed that the prevalence of coccidiosis in the Jember District reached 20% with a mild category of infection.